Senam Indonesia Hebat: Integrasi Aktivitas Fisik dan Pendidikan Jasmani di Sekolah Dasar - Anggraeni, Emayanti; Fadjri, Mukharrar; Istiyono, Abu; Umpes, Aplos; Ismi Mori Saputra, Deka (Jurnal Muara Olahraga, 2025)
Physical education in elementary schools plays a crucial role in developing healthy lifestyle habits and improving children's physical fitness. The Senam Indonesia Hebat (Great Indonesian Gymnastics) program is a structured physical activity innovation that can be integrated into physical education (PJOK) learning to improve motor skills, physical activity, and reduce students' sedentary behavior. This study used a quasi-experimental design with two groups: an experimental group that participated in an eight-week gymnastics program and a control group that continued with conventional PJOK learning. The sample consisted of 60 fourth-sixth grade elementary school students. Data were collected through physical fitness tests, physical activity questionnaires, and observations of sedentary behavior, then analyzed using descriptive analysis and t-tests. The results showed a significant increase in the experimental group compared to the control group, both in muscle strength (24.7 ± 3.5 vs. 20.1 ± 3.2), endurance (17.6 ± 3.1 vs. 14.0 ± 2.8), agility (18.4 ± 2.9 vs. 15.2 ± 2.6), balance (14.9 ± 2.4 vs. 12.0 ± 2.1), duration of physical activity (78 ± 12 minutes/day vs. 55 ± 10 minutes/day), and reduction in sedentary behavior (145 ± 15 minutes/day vs. 195 ± 16 minutes/day). The results of this study prove that the integration of Senam Indonesia Hebat into PJOK learning is effective in improving physical fitness and can encourage physical activity in elementary school students. Keywords: Senam Indonesia Hebat, Physical Education, Physical Activity, Elementary School